2020
DOI: 10.14336/ad.2019.0511
|View full text |Cite
|
Sign up to set email alerts
|

The Paradoxical Effect of Deep Brain Stimulation on Memory

Abstract: Deep brain stimulation (DBS) is a promising treatment for many memory-related disorders including dementia, anxiety, and addiction. However, the use of DBS can be a paradoxical conundrumdementia treatments aim to improve memory, whereas anxiety or addiction treatments aim to suppress maladaptive memory. In this review, the key hypotheses on how DBS affects memory are highlighted. We consolidate the findings and conclusions from the current research on the effects of DBS on memory in attempt to make sense of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 127 publications
4
17
0
Order By: Relevance
“…An early hypothesis of the mechanism of DBS was that it creates a temporary neural activity lesion, and we further showed that prelimbic cortex DBS was associated with the disruption of memory and a drop in the neural activity marker c-fos in the ventral hippocampus [6]. Dropout of neural nodes, while congruent with the disruption of memory, has not played a major role in the mechanistic understanding of memory enhancement seen in DBS (though it should be noted that other mechanism such as neurogenesis and wave syncing have been suggested [3]). In this paper, we propose that DBS causes dropout in neural nodes that "forces" the activation of new pathways and creates more robust networks, similar to how dropout enhanced the neural networks.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…An early hypothesis of the mechanism of DBS was that it creates a temporary neural activity lesion, and we further showed that prelimbic cortex DBS was associated with the disruption of memory and a drop in the neural activity marker c-fos in the ventral hippocampus [6]. Dropout of neural nodes, while congruent with the disruption of memory, has not played a major role in the mechanistic understanding of memory enhancement seen in DBS (though it should be noted that other mechanism such as neurogenesis and wave syncing have been suggested [3]). In this paper, we propose that DBS causes dropout in neural nodes that "forces" the activation of new pathways and creates more robust networks, similar to how dropout enhanced the neural networks.…”
Section: Discussionmentioning
confidence: 73%
“…We have previously argued that timing plays an important role in the outcome of DBS on memory [3]; DBS applied post or during behaviour testing tended to disrupt memory, whereas DBS applied prior to behaviour testing tended to enhance memory. However, the mechanisms behind these outcomes are still relatively unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously argued that timing plays an important role in the outcome of DBS on memory (Tan et al, 2020b ). DBS applied post or during behavior testing tended to disrupt memory, whereas DBS applied prior to behavior testing tended to enhance memory.…”
Section: Discussionmentioning
confidence: 99%
“…However, memory systems can fall into disease when expressed pervasively (e.g., anxiety or addiction) or degenerate (e.g., dementia)—both of which are major health challenges worldwide (World Health Organization, 2012 , 2017 ). Neuromodulation techniques such as deep brain stimulation (DBS) have shown promising results as treatments for memory-related disorders (Tan et al, 2019b , 2020b ), yet the mechanisms behind these effects are still largely unknown. Furthermore, the effects of treatments such as DBS appear to be paradoxical, in that they can both disrupt (Hamani et al, 2010 ; Tan et al, 2019a ) and enhance memories (Hamani et al, 2011 ; Tan et al, 2020c ) even when applied to the same brain target (detailed review in Tan et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%